2020
DOI: 10.1017/s1092852920002126
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Spectrum disorders in Parkinson’s disease: a systematic evaluation

Abstract: Objective Psychiatric disorders are very common in patients affected by Parkinson’s disease (PD). However, comorbidity with Bipolar Spectrum disorders is understudied. The aim of this study is to explore the clinical correlates of PD associated with Bipolar Spectrum disorders. Methods One hundred PD patients were screened for psychiatric comorbidities, cognitive profile, motor, and non-motor symptoms. The sample was divided into three groups: PD-patients with Bipolar Spectrum disorders (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…According to MINI-Plus, 42 patients had a history of a depressive episode, 26 of which met criteria for major depressive disorder. As previously reported, bipolar spectrum disorders (i.e., including drug-induced hypomania and unipolar hypomania) were diagnosed in 32 patients according to SIMD-R [ 25 ]. Overall, 26 (26%) patients were currently diagnosed with at least one anxiety disorder according to MINI-Plus, with GAD being the most frequent current anxiety disorder (15 of 100, 15%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to MINI-Plus, 42 patients had a history of a depressive episode, 26 of which met criteria for major depressive disorder. As previously reported, bipolar spectrum disorders (i.e., including drug-induced hypomania and unipolar hypomania) were diagnosed in 32 patients according to SIMD-R [ 25 ]. Overall, 26 (26%) patients were currently diagnosed with at least one anxiety disorder according to MINI-Plus, with GAD being the most frequent current anxiety disorder (15 of 100, 15%).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, both patients with current anxiety disorders and patients who have ever satisfied criteria for panic disorder and/or agoraphobia over the course of life were included among patients with lifetime anxiety disorders. Other assessment instruments and further details on recruitment were previously described by Bacciardi et al [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…These studies suggested that the prevalence of BSDs in PD is higher than in control populations. Following the epidemiological reports, new studies addressed BSDs in PD, generically naming the described disorders as hypomania 42‐45 . Guided by earlier literature, 8‐27 and also because, in several legal instances, two senior authors of the present paper were asked to provide an earnest analysis for compensation claims, which were at the time prevalent on social and public media, 46‐49 we started testing all PD patients in our cohort using psychiatric scales and interviews to assess BSDs.…”
mentioning
confidence: 99%
“…Following the epidemiological reports, new studies addressed BSDs in PD, generically naming the described disorders as hypomania. 42 , 43 , 44 , 45 Guided by earlier literature, 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 and also because, in several legal instances, two senior authors of the present paper were asked to provide an earnest analysis for compensation claims, which were at the time prevalent on social and public media, 46 , 47 , 48 , 49 we started testing all PD patients in our cohort using psychiatric scales and interviews to assess BSDs. When the last epidemiological studies were published, 35 , 36 we thought we could present our data for discussion.…”
mentioning
confidence: 99%
“…Parkinson's disease (PD), historically defined as a movement disorder, is now considered the prototypical neuropsychiatric condition, in which motor signs, such as tremors, rigidity, and bradykinesia, occur together with cognitive and neuropsychiatric features [6]. Depression [7], bipolar disorder [8,9], psychosis [10], anxiety [11], impulse control disorders [12], apathy [13], and sleep disturbances [14] can frequently and significantly impact the course of PD. Despite the high psychiatric comorbidity reported in PD patients, few cases of catatonia have been reported in the literature [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%